Microstructural Behaviors of Matrices Based on Polylactic Acid and Polyhydroxyalkanoates - Alzate Marin, Juan Carlos (2018)
Individual films of polyhydroxyalkanoates (PHA) and polylactic acid (PLA) and their blends were developed by solvent casting. PHA was obtained from activated sludges from a wastewater-treatment system at a laboratory scale. This work focused on analyzing the microstructural properties and thermal behaviors of individual films of PHA and PLA as well as those of their blends. The behaviors of the biodegradation processes of the individual films and blends were examined from a microstructural point of view. ATR-FTIR spectra indicated the existence of weak molecular interactions between the polymers. The formulation of blend films improved the crystallinity of PLA; additionally, it induced the polymer-recrystallization phenomenon, because crystallized PHA acted as a PLA-nucleating agent. This phenomenon explains the improvements in the films´ water-vapor-barrier properties. The blends exposed to a biodegradation process showed an intermediate behavior between PLA and PHA, leading to a consistent basis for designing systems tailored to a particular purpose.